(untitled) (St. Paul, MN, 2006)
Much more than a traditional casebook, this exciting new text speaks the language that is most easily comprehended by the current generation of law students. Web resources, rich visual aids, and articles from recent periodicals are interspersed throughout the text, all with the aim of better enabling students to grasp key concepts and practical applications of this continually evolving and changing field of law. This comprehensive text covers all the traditional topics that are included in natural resources classes. In addition, it focuses on every level of natural resource ownership: federal, tribal, private, and state. The book also includes an extensive discussion of the economic aspects of natural resources law and policies.
Keywords: Natural resources,Nguồn tài nguyên thiên nhiên; Law and legislation,Pháp chế và luật pháp; United States,Hoa Kỳ